1993
DOI: 10.1111/j.1360-0443.1993.tb02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a sample of convicted drinking drivers

Abstract: Mortality rates for 639 drinking drivers were calculated. The sample consisted of all individuals convicted of a second offence in two Ontario cities (Oshawa and North Bay) between 1973 and late 1978. There were 53 deaths (51 males, 2 females) in the sample prior to the end of 1986. Among males, significant excess total mortality was observed (Standardized Mortality Ratio = 1.7); similar trends were observed among females. Age-related excess mortality and excess mortality by cause were strikingly similar to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…A LARGE BODY of research demonstrates a strong link between alcohol use and violence. Individuallevel studies show that individuals who have consumed alcohol are more likely to commit violent acts, individuals who are seen in hospitals as a result of violent acts are more likely to have been drinking, individuals who have committed a violent act were frequently under the influence of alcohol when the act occurred, and finally, heavy, abusive, or alcoholic drinkers are more likely to die from accidental and violent causes (e.g., Graham et al, 1998;Mann et al, 1993;Pernanen, 1991;Wells et al, 2000). While the causal pathways in alcohol-related violence are not fully understood, it is clear that alcohol use is associated with increased likelihood of various forms of violence, including homicide (Parker and Auerhahn, 1998;Pernanen, 1991;Wells et al, 2000).…”
mentioning
confidence: 99%
“…A LARGE BODY of research demonstrates a strong link between alcohol use and violence. Individuallevel studies show that individuals who have consumed alcohol are more likely to commit violent acts, individuals who are seen in hospitals as a result of violent acts are more likely to have been drinking, individuals who have committed a violent act were frequently under the influence of alcohol when the act occurred, and finally, heavy, abusive, or alcoholic drinkers are more likely to die from accidental and violent causes (e.g., Graham et al, 1998;Mann et al, 1993;Pernanen, 1991;Wells et al, 2000). While the causal pathways in alcohol-related violence are not fully understood, it is clear that alcohol use is associated with increased likelihood of various forms of violence, including homicide (Parker and Auerhahn, 1998;Pernanen, 1991;Wells et al, 2000).…”
mentioning
confidence: 99%
“…It is this same profile that produces high follow-up mortality rates, particularly among drivers arrested with high BACs (Mann, Anglin, Wilkins, Vingilis, & MacDonald, 1993;Skurtveit, Christophersen, Grung, & Mørland, 2002). The high auto fatality rate of HCDDs is related to both their risk-taking behavior while intoxicated and their failure to wear seat belts.…”
Section: Broader Clinical Profilementioning
confidence: 97%
“…Mortality studies have demonstrated that heavy drinkers and alcoholics die from cirrhosis at a much higher rate than the general population 40,48,49,50 . Alcohol has consistently been related to the risk of malignancy like cancer of the mouth (lip, tongue), pharynx, larynx, hypopharynx, oesophagus and liver [51][52][53][54] .…”
Section: Spectrum Of Alcoholic Liver Diseasementioning
confidence: 99%